1994
DOI: 10.1111/j.1469-8749.1994.tb11793.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subjective and Objective Measures of Movement Performance in Children With Cerebral Palsy

Abstract: SUMMARY This study evaluated the use of accelerometry to measure the quality of movement in children with cerebral palsy. Accelerometer scores based on a previously described test were correlated with scores on a newly developed clinical test shown to be both valid and reliable. Low correlations were obtained between clinical test scores and accelerometer scores. Although the accelerometer test has been shown to be effective in distinguishing between able‐bodied children and those with cerebral palsy, it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Following a comprehensive review of existing evaluation tools, the PEDI was selected for comparison on the basis of the fact that it had been validated, had been used as a benchmark for the validation of other tools, and was familiar to the occupational therapists at our institution following its use in a previous study 38,42,49,56 . The JTT was also selected for the determination of concurrent validity for similar reasons, including its widespread use in the literature and its consideration of nondominant extremity function 33,37,40,48,50,54 . The fair correlation between the self-care scaled score of the PEDI and the spontaneous functional analysis score of the SHUEE was a consequence of a narrow range of relatively high scores on the PEDI and a wider range of scores on the SHUEE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a comprehensive review of existing evaluation tools, the PEDI was selected for comparison on the basis of the fact that it had been validated, had been used as a benchmark for the validation of other tools, and was familiar to the occupational therapists at our institution following its use in a previous study 38,42,49,56 . The JTT was also selected for the determination of concurrent validity for similar reasons, including its widespread use in the literature and its consideration of nondominant extremity function 33,37,40,48,50,54 . The fair correlation between the self-care scaled score of the PEDI and the spontaneous functional analysis score of the SHUEE was a consequence of a narrow range of relatively high scores on the PEDI and a wider range of scores on the SHUEE.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized clinical tests of hand and upper extremity function in children have been developed to improve the quality of the information that is available for clinical decisionmaking and outcome assessment 14,[32][33][34][35][36][37][38][39][40][41][42][43] . Such tests typically have focused on elements of impairment, with little emphasis on the assessment of disability and societal limitations.…”
mentioning
confidence: 99%
“…The Melbourne Assessment was developed to measure function in children with cerebral palsy (Bach, Reddihough, Burgess, Johnson, & Byrt, 1994, Reddihough, Bach, Burgess, Oke, & Hudson, 1990. The test-retest reliability of the Melbourne Assessment consisted of a study population of 20 children with cerebral palsy of varying types and severity and indicated that the Melbourne Assessment was highly reliable with the sample population.…”
Section: Methodsmentioning
confidence: 99%
“…The Melbourne Assessment was developed and designed by two occupational therapists and a paediatrician, following extensive investigation of techniques for objectively measuring upper-limb movement in children with CP (Reddihough et al 1987(Reddihough et al , 1990(Reddihough et al , 1991Bach et al 1994). The Melbourne Assessment has three purposes as detailed in the manual.…”
Section: Psychometric Properties Of the Melbourne Assessmentmentioning
confidence: 99%